(untitled) (Research, Society and Development, 2022)
Considering the level of abstraction of chemical knowledge and the importance of knowledge of chemical bonds content for the appropriation of many other concepts, the present work aims to carry out a systematic review of the literature on methodologies for teaching chemical bonds that have approaches different from the traditional one. and that seek a better relationship between teaching and learning for basic education students. The searches were carried out in the Portal of Periodicals of the Coordination for the Improvement of Higher Education Personnel (CAPES) using teaching methodology, teaching chemistry and chemical bonds as descriptors. We found 8 articles considered relevant to the research, most of which used playful approaches and through games, resulting in an improvement in the level of student learning. Considering the little literature available on the subject, especially in Elementary School, it is recommended to carry out new researches that analyze methodologies that provide students with more significant learning.